Róża Wojciecha Smarzowskiego jako medium idei - SZPULAK, ANDRZEJ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Wojciech Smarzowski’s Rose as the medium of ideology The text concentrates on the problem of the ideologization of artistic transmission and uses Wojciech Smarzowski film ‘Rose’ as an example. This problem is considered both on several levels: reception, above all the critical-film level, and also on the level of the work itself. The analysis reveals the impoverishment of the message by radical left-wing and also conservative ideologization is becoming apparent. Also a susceptibility of work to discourse of the political correctness is becoming apparent, in addition it is rather superficial susceptibility.